Design of a Semi-Inverse Taper Horizontal Blade Wind Turbine and Its Potential use at Gajah Beach Padang - Putri Pratiwi; Frizky Yurian (Jurnal Teknik Mesin, 2021)
The development of the use of wind energy to produce electrical is still quite attractive, especially in developing country such as Indonesia. Padang City is an area located on the west coast of Indonesia and is influenced by west, southwest, northwest winds with low wind with speeds ranging from 2 m/s to 10 m/s. The purpose of this research is to design a blade that can rotate in that speed range. The blade designed is a semi-inverse taper with a chord ratio of 1:1,3, the length of the blade is 90 cm. The design showed that the highest peak was found at 51% at TSR 4.5. Assuming a maximum generator speed of 500 rpm and the range of wind speeds from 1 m/s to 12 m/s, it is known that the blades begin to rotate at 2.1 m/s, the maximum power is 1324 Watts when the wind speed is 12 m/s